Anti-allergic Potential of Methanolic Extracts of Leaves and Fruit of Gmelina arborea Roxb - Chothani, Daya L; Patel, NM (Asian Journal of Biological and Life Sciences)
Objectives: An anti-allergic study was performed on a methanolic extract of leaves (GLA) and fruit (GFA) of Gmelina arborea Roxb. (Verbenaceae). Methods: Anti-allergic study was evaluated using an isolated guinea pig ileum, isolated rat ileum preparation and passive paw anaphylaxis in rats. The effect of methanolic extracts (100, 200 μg/ml) of the fruit and leaves were studied on contraction induced by histamine and acetylcholine on isolated guinea pig ileum and isolated rat ileum, respectively. The inhibition of paw volume was studied (100, 300mg/kg GLA and 100, 300mg/kgGFA, p.o.) and compared with vehicle treatment. Dexamethasone (0.27mg/kg, p.o.) was included as a positive control. Results: GLA and GFA showed significant inhibitory contraction of guinea pig ileum (p<0.01, p<0.005), rat ileum and (p< 0.01, p<0.005) rat paw volume inhibition. Conclusion: The anti-allergic activity of methanolic extracts of the fruit (GFA) and leaves (GLA) of G. arborea may be due to presence of phenolic and flavonoid compounds. The effects are noteworthy and highlight these extracts for further studies.
Keywords: Anti-allergic activity; Acute toxicity Gmelina arborea; Passive paw anaphylaxis; Phytochemical screenig.